Correlation between pubic bone mineral density and age from a computed tomography sample. (May 2019) - Dubourg, Olivier; Faruch-Bilfeld, Marie; Telmon, Norbert; Maupoint, Estelle; Saint-Martin, Pauline; Savall, Frédéric
Highlights: The estimation of age at death is mainly required to establish a biological profile. This study aimed to test the evolution of pubic bone mineral density with the age. This work presents a creative method using phantoms to calibrate bone density values. Bone density could constitute a useful quantitative parameter for age estimation. Bone density could represent the "numerical equivalent" of dry bones features. Abstract: In forensic anthropology, the estimation of age at death is mainly required to establish a biological profile and facilitate individual identification. The Suchey–Brooks (SB) system represents one of the most commonly used and tested methods of assessment based on the morphological characteristics of the pubic symphysis. However, this method has certain drawbacks, including frequently inaccurate estimation for older individuals. The aim of this work was to test the evolution of pubic bone mineral density (BMD) according to age, especially for individuals over 40 years old. We retrospectively studied pubic bones from males (n = 88) and females (n = 113) over 40 years of age undergoing clinical multi-slice computed tomography (MSCT) in a French hospital between November 2017 and April 2018. The results revealed a significant negative correlation between BMD and age for males (R = −0.62) and females (R = −0.55). The intra- and inter-observer reliabilities of the phase allocation were moderate for males (kappa values at 0.72 and 0.65) and strong for females (kappa values at 0.93 and 0.86). Moreover, a significant difference in BMD between stages 6-1 and 6-2 for males was observed. We hypothesize that BMD might help improve the reliability of the SB system for older individuals. In addition to the pubic bone, numerous other anatomical regions such as the area of Ward could represent interesting areas of study in order to relate bone density to age.